HIV/AIDS – criminological analysis of the identity of criminal and the victims’ connection with infection of human immunodeficiency virus (Journal of actual problems of jurisprudence, 2018)
The purpose of article – studying the identity of criminal and victims’ connection with infection of human immunodeficiency virus (HIV/AIDS) from criminological positions.By basis of analysis individual social and demographic, psychological, biological persons’ signs, authors recreate a portrait criminal’s identity – the person who has a certain type of criminal behavior consciously posing itself threat of epidemic’s distribution – HIV/AIDS, harm to health, threat to healthy people’s life also. By the way, according to art. 118 of the Criminal Code of Kazakhstan, authors developed identity typology of criminal and crimes’ victims’.Authors think that according to Art. 118 of the Criminal Code of Kazakhstan criminal’s behavior caused by victim’s behavior and relationship of criminal with victim which developed earlier or in the course of collision. According to of researchers, upon to 29% of crimes either are provoked by the victims,or are made with their assistance.By the researchers’ point of view, result of studying the crimes’ victims’ are necessary in disclosure,investigation and prevention of crimes connected with infection of HIV/AIDS. Cause it is impossible toconnect criminals’ importance and victims which given persons only with prevention of crimes, anddescribing the characteristic of persons only by psychology. Relevant data’s psychological importancedoes not cancel their criminal and legal, criminality and procedural importance.Key words: identity of criminal, typology of criminal’s identity, crime’s victim, typology victim’scrime, victim, victim’s behavior.